ChemInform Abstract: Efficient Synthesis of Conformationally Restricted Apoptosis Inhibitors Bearing a Triazole Moiety. Issue 8 (February 2016) - Corredor, Miriam; Garrido, Maria; Bujons, Jordi; Orzaez, Mar; Perez‐Paya, Enrique; Alfonso, Ignacio; Messeguer, Angel
Abstract: Using an Ugi four‐component reaction and subsequent treatment of the crude products with base allows the synthesis of β‐lactams (V) and/or pyridazinediones.